Risk Factors Associated with Mother-to-Child Transmission of HIV in Dar es Salaam, Tanzania - Elias, Felix; Shaban, Nyimvua; Rutalebwa, Edwin (Tanzania Journal of Science, 2021)
Despite Tanzania's efforts and substantial progress in PMTCT, about 11% new infections were recorded among Tanzanian children in 2019 (UNAIDS 2020a). The objective of this study was to determine the rate of HIV transmission and to identify its risk factors among HIV exposed infants born to HIV-positive mothers in Dar es Salaam, Tanzania. A cross-sectional study was conducted using retrospective data collected from HIV-positive mothers and their exposed babies who were followed and registered in health facilities in four administrative districts (Ilala, Temeke, Kinondoni, and Ubungo) in Dar es Salaam between January 2016 and December 2019. To identify risk factors for MTCT, univariate and multivariate Cox Proportional hazard regression analyses were employed. Out of 18705 registered children exposed to HIV, 586 (3.1%) were positive during the study period, while 18119 (96.9%) were negative. In this study, the following factors were increasing the risks of MTCT of HIV infections, not receiving ARV prophylaxis right at birth (aHR = 2.39, 95% CI: 1.75–3.26, P < 0.001), unsuppressed maternal viral load (aHR = 6.26, 95% CI: 4.91–7.97, P < 0.001), WHO clinical stage 3–4 (aHR = 1.79, 95% CI: 1.44–2.23, P < 0.001), and mixed feeding (aHR = 4.09, 95% CI: 1.80–9.31, P < 0.001). The factors maternal age group 25–34 years (aHR = 0.47, 95% CI: 0.29–0.75, P < 0.001), being married/cohabiting (aHR = 0.47, 95% CI: 0.23–0.95, P = 0.036), duration on ART for > 12 months (aHR = 0.55, 95% CI: 0.45–0.67, P < 0.001), dried blood spot (DBS) tested at 6 weeks (aHR = 0.09, 95% CI: 0.04–0.18, P < 0.001), and exclusive replacement feeding (ERF) (aHR = 0.32, 95% CI: 0.17–0.60, P < 0.001) decreased the risk of MTCT of HIV infections. These findings indicated that further work is required to scale up PMTCT approaches to concentrate on viral load suppression, taking ARV prophylaxis immediately at birth, and EBF practice in the first 6 months of life. Keywords: HIV, PMTCT, risk factors, mother-to-child transmission (MTCT)